A Model of Teaching Practices for Results-based Accreditation in Engineering Careers - Pizarro-Aguilar, Melissa (2022)
Objective. This work consists of a state of the question created to understand how teaching practices guide the development of the training process for the completion of the professional profile in engineering careers. Analysis. Writing this paper began with a bibliographic review of academic articles from the best-positioned journals in engineering education, considering publications from 2008 to 2018. Subsequently, in the selected publications, common lines of research are determined. In each of these, coincidences and differences in the theoretical and methodological approaches and the main findings are identified. Results. This article includes a discussion on the characterization of competencies or attributes in the engineering knowledge area and the identification of two important lines of research: the implementation of teaching practices for the development of specific competence and the understanding of the actors’ beliefs regarding the development of competencies or attributes. These lines are related since they can be considered as stages of a systematic improvement process for teaching practices based on the feedback obtained from the various perceptions of the actors. However, it is identified that they have not been addressed in an integrated manner from empirical research yet. Conclusions. Based on the findings and good practices identified through the analyzed empirical research, a model of teaching practices can be proposed for result-based accreditation, which includes a cycle of integration of the attributes comprising an improvement process where three pillars stand out: theoretical bases, teaching and learning, and the evaluative framework.